Therapeutic approach to pain in neurodegenerative diseases: current evidence and perspectives. (1st February 2017) - de Tommaso, Marina; Kunz, Miriam; Valeriani, Massimiliano
ABSTRACT: Introduction : Neurodegenerative diseases are increasing in parallel to the lengthening of survival. The management of Alzheimer's disease (AD) and other dementias, Parkinson's disease (PD) and PD-related disorders, and motor neuron diseases (MND), is mainly targeted to motor and cognitive impairment, with special care for vital functions such as breathing and feeding. Areas covered : The present review focuses on chronic pain in main neurodegenerative diseases, addressing current evidence on pain therapeutic management, pain frequency and clinical features, and possible pathophysiological mechanisms. The search on PubMed had no time limits and was performed by searching for the following key issues: pain, dementia, Alzheimer disease, Parkinson's disease, extrapyramidal disorders, motoneuronal disease, Amyotrophic lateral sclerosis, FXTAS, frequency, pathophysiology, treatments, therapy, efficacy, opioids, side effects. No controlled therapeutic trials and guidelines are currently available. The effects of current therapies such as L-Dopa or riluzole on pain symptoms are not clear. Emerging evidences on the possible anti-nociceptive effects of cannabis or botulinum toxin might be available soon. Expert commentary : Pain needs to be better evaluated and fully considered in the global management of neurodegenerative disease because a more focused treatment may have a positive impact on the global burden of these devastating disorders.